Supporting Active Living Through Community Plans: The Association of Planning Documents With Design Standards and Features. Issue 2 (February 2019) - Peterson, Erin L.; Carlson, Susan A.; Schmid, Thomas L.; Brown, David R.; Galuska, Deborah A.
Purpose: The purpose of this study was to examine the association between the presence of supportive community planning documents in US municipalities with design standards and requirements supportive of active living. Design: Cross-sectional study using data from the 2014 National Survey of Community-Based Policy and Environmental Supports for Healthy Eating and Active Living. Setting: Nationally representative sample of US municipalities. Participants: Respondents are 2005 local officials. Measures: Assessed: (1) The presence of design standards and feature requirements and (2) the association between planning documents and design standards and feature requirements supportive of active living in policies for development. Analysis: Using logistic regression, significant trends were identified in the presence of design standards and feature requirements by plan and number of supportive objectives present. Results: Prevalence of design standards ranged from 19% (developer dedicated right-of-way for bicycle infrastructure development) to 50% (traffic-calming features in areas with high pedestrian and bicycle volume). Features required in policies for development ranged from 14% (short/medium pedestrian-scale block sizes) to 44% (minimum sidewalk widths of 5 feet) of municipalities. As the number of objectives in municipal plans increased, there was a significant and positive trend ( P < .05) in the prevalence of each design standard and requirement. Conclusions: Municipal planning documents containing objectives supportive of physical activity are associated with design standards and feature requirements supportive of activity-friendly communities.